Development of temporary subtropical wetlands induces higher gas production - Canterle, Eliete R.; Motta Marques, David d.; Rodrigues, Lúcia R. (Frontiers in Microbiology, 2013)
Temporary wetlands are short-term alternative ecosystems formed by flooding for irrigation of areas used for rice farming. The goal of this study is to describe the development cycle of rice fields as temporary wetlands in southern Brazil, evaluating how this process affect the gas production (CH4 and CO2) in soil with difference % carbon and organic matter content. Two areas adjacent to Lake Mangueira in southern Brazil were used during a rice-farming cycle. One area had soil containing 1.1% carbon and 2.4% organic matter, and the second area had soil with 2.4% carbon and 4.4% organic matter. The mean rates of gas production were 0.04 ± 0.02 mg CH4 m-2 d-1 and 1.18 ± 0.30 mg CO2 m-2 d-1 in the soil area with the lower carbon content, and 0.02 ± 0.03 mg CH4 m-2 d-1 and 1.38 ± 0.41 mg CO2 m-2 d-1 in the soil area with higher carbon content. Our results showed that mean rates of CO2 production were higher than those of CH4 in both areas. No statistically significant difference was observed for production of CH4 considering different periods and sites. For carbon dioxide, however, a two-way ANOVA showed statistically significant difference (p=0.05) considering sampling time, but no difference between areas. The results obtained suggest that the carbon and organic matter contents in the soil of irrigated rice cultivation areas may have been used in different ways by soil microorganisms, leading to variations in CH4 and CO2 production.